Communication Challenges at the Crossroads of Oncology and Palliative Care: Finding a Way Forward When Clinicians Differ on Prognosis. Issue 4 (October 2019) - Collins, Molly E.; Abrahm, Janet L.
In this article, we present a dialogue between a junior and a seasoned palliative care attending on approaching situations in which clinicians have differing opinions about patients' prognoses. In such situations, we may find a way forward by identifying common ground and exploring patients' and clinicians' values. Specifically, we can ask what constitutes a reasonable quality of life for our patients, and we can explore our colleagues' hopes, worries, and values using familiar communication techniques. Ultimately, we can support and align with both our patients and colleagues and work toward reframing a difficult situation.